Application of Seismic Geomorphology for Exploration: Example of Block PM318, Malay Basin - BIN ABDUL MALIK, MUHAMMAD HAZMI (Universiti Teknologi PETRONAS, 2016)
This research paper is focusing on the structural geomorphology Block PM318, Malay Basin. Block PM318 is located at the north part of Malay Basin. Based on the research paper, most of the development well found the hydrocarbon in stratigraphy trap. There were several discovered well drilled within this block which shown hydrocarbon indication. Since there is still a lot area that not been explored, therefore the author interested to study the geological in this area as he belief there are still plenty of hydrocarbon potential in this block. For the Final Year Project 1, the author successfully interpret the geomorphology of the subsurface by using seismic attribute. Due to the limited resolution, the author can only interpret at the shallow part of the subsurface and interpret lots of channels geomorphology located 1200m under the subsurface. The result given also satisfied as it shows the pathway of the channel and also positive value for Direct Hydrocarbon Indicator (DHI). Seismic inversion helps the author to determine the lithology that filled the channel by using post stack inversion method. From the result, the author can proved the channel is a heterogeneous sand prone area.